Prevalence of Met-203 type spaA variant in Erysipelothrix rhusiopathiae isolates and the efficacy of swine erysipelas vaccines in Japan - Uchiyama, Mariko; Yamamoto, Kinya; Ochiai, Mariko; Yamamoto, Tsukasa; Hirano, Fumiya; Imamura, Saiki; Nagai, Hidetaka; Ohishi, Kouji; Horiuchi, Noriyuki; Kijima, Mayumi (Biologicals, 2014)
Since 2009, erysipelas infection among pigs in Japan has been increasing. This study investigated the prevalence, and characteristics of Erysipelothrix rhusiopathiae isolates in Japan from 2008 to 2010 and assessed the efficacy of current commercial erysipelas vaccines. Based on polymorphisms in a 432-bp hypervariable region in the surface protective antigen A (spaA) gene, 34 isolates were classified into three groups: (i) Group 1 with methionine at position 203 (Met-203) and isoleucine at position 257 (Ile-257) (18 isolates of serotype 1a and one untypable isolate). (ii) Group 2 with Ile-257 (12 isolates of serotypes 1a, 1b, 2, 10 and 11), and (iii) Group 3 with alanine at position 195 (Ala-195) and Ile-257 (three isolates of serotype 1a). Isolates with Met-203 were highly pathogenic in mice and pigs, causing death in the pig and LD50 values of 0.45–1.45 CFU per mouse. One live and three inactivated commercial E. rhusiopathiae vaccines were evaluated for efficacy against a Met-203 isolate. Almost all mice and pigs that received vaccine survived, while non-vaccinated controls all died within 5 days of the challenge. This indicates that swine erysipelas vaccines might be still effective in protecting animals against the recently prevalent Met-203 isolates in Japan.